G Protein-Coupled Estrogen Receptor: A Potential Therapeutic Target in Cancer - Xu, Shen; Yu, Shan; Dong, Daming; Lee, Leo Tsz On (Frontiers in Endocrinology, 2019)
The G protein-coupled estrogen receptor (GPER) is a seven-transmembrane-domain receptor that mediates non-genomic estrogen related signaling. After ligand activation, GPER triggers multiple downstream pathways that exert diverse biological effects on the regulation of cell growth, migration and programmed cell death in a variety of tissues. A significant correlation between GPER and the progression of multiple cancers has likewise been reported. Therefore, a better understanding of the role GPER plays in cancer biology may lead to the identification of novel therapeutic targets, especially among estrogen-related cancers. Here, we review cell signaling and detail the functions of GPER in malignancies.